COMMODIFICATION OF TUTURANGIANA ANDALA RITUAL PERFORMED BY COMMUNITY OF FISHERMEN, BAUBAU CITY, MAKASAR ISLAND, SOUTHEAST SULAWESI PROVINCE - Syahrun, Syahrun Syahrun; Kembara, A.A. Ngurah Anom; Cika, I Wayan Cika; Sukarja, Putu Sukarja (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2015)
Tuturangiana andala ritual is a tradition of floating offerings which have been performed from generation to generation by the community of fishermen in Makassar Island. It used to be simply performed; however, being commodified, it had been performed more lively than before. The government of Baubau City had modified it; everything had been transformed into commodities. The problems arised were analyzed using the theory of semiotics, the theory of rites, and the theory of discourse of power and knowledge. The data were obtained through interview, observation, and documentation. The result of the study shows: first, the process of commodification could not be separated from the process of production, the process of distribution and the process of consumption of the tuturangiana ritual. What was produced for the performance of the tuturangiana andala ritual was the place where it was performed, the things needed for the offerings, the clothing, the dance and the music instrument. The commodified tuturangiana andala ritual was distributed through media and direct communication. It was consumed by the people living in Makassar Island and the local government for tourism. Second, the commodified tuturangiana andala ritual contained (1) the philosophical meaning, (2) the economic meaning, (3) the political meaning, (4) the cultural conservation. Third, the commodified tuturangiana ritual affected the components of the social cultural system of the community of fishermen in Makassar Island such as the common ideology, religion, art, politics, social stratification, technology, economy, and ecology.